Alterations in Mycelial morphology and flow cytometry assessment of membrane integrity of Ganoderma boninense stressed by phenolic compounds - Ganapathy, Daarshini; Siddiqui, Yasmeen; Ahmad, Khairulmazmi; Adzmi, Fariz; Kong, Lih Ling (Multidisciplinary Digital Publishing Institute, 2021)
Global increase in demand for palm oil has caused an intensification in oil palm plantation; however, production is greatly hindered by Basal Stem Rot (BSR) disease caused by Ganoderma boninense. There are many approaches to controlling BSR, although, there is no accurate, sustainable and effective method to suppress G. boninense completely. Hence, four phenolic compounds [Gallic acid (GA), Thymol (THY), Propolis (PRO) and Carvacrol (CARV)] were selected to evaluate their antifungal effect, ability to alter the mycelium morphology, and fungal cell integrity against G. boninense. Significant differences (p < 0.05) were observed and 94% of inhibition was exerted by GA on G. boninense growth. Scanning Electron Microscopy and High-Resolution Transmission Electron Microscopy observations revealed that GA and THY treatment caused severe damage to the mycelium and recorded the highest amount of sugar and electrolyte leakage. The study of cell integrity and morphological disruption has elucidated the reduction of G. boninense cell viability. Generally, our findings confirm the fungistatic effects of GA and THY. The evolution of phenolic compounds during the phytopathology studies indicated their coherence in eradicating the G. boninense. It is proposed that GA and THY had the potential to be developed further as a natural antifungal treatment to suppress G. boninense.